Methods Of Using Statistical Data In The Lessons Of Economic And Social Geography - Djumabaeva Salomat Komiljonovna (Genius Journals, 2022)
The article describes the methodology of using statistical data in the lessons of economic and social geography. The issues of developing knowledge and skills of geographical students of higher education institutions in mastering statistical methods are analyzed.
Keywords: Geography; Statistics; Methodology; Research